Psychometric properties of a spanish version of the experiences in close relationships-revised scale [Propiedades psicométricas de una versión en español del experiences in close relationships-revised (ECR-R)] - Nóblega, Magaly (2020)
ABSTRACT This research explored evidences of internal structure and convergent validity as well as reliability of a Spanish version of the Experiences in Close Relationships-Revised (ECR-R) in Peruvian college students. Exploratory and confirmatory factor analyses were carried out sequentially in two randomly assigned sub-groups (n = 289, n = 301). Horn’s parallel analysis and exploratory factor analysis performed with the first subgroup found a structure of three factors (anxiety, avoidance directly measured and avoidance inversely measured). Then, confirmatory factor analysis carried out with the second sub-group replicated a three-factor model with acceptable adjustment indices. Each dimension showed good internal consistency trough Cronbach’s alpha coefficient. The results partially support convergent validity of the ECR-R with the Relationship Questionnaire. Finally, a 27-item Spanish ECR-R version with acceptable evidence of internal structure and convergent validity is presented.